2020
DOI: 10.1002/mnfr.201901019
|View full text |Cite
|
Sign up to set email alerts
|

DietaryAdvancedGlycationEnd Products–InducedCognitive Impairment in Aged ICR Mice: Protective Role of Quercetin

Abstract: Scope: Dietary advanced glycation products (dAGEs) have been reported to induce cognitive impairment while quercetin possesses potential neuroprotective effects. The aim is to explore whether dAGEs would induce similar cognitive impairment from both young and aged ICR mice, and the protective effects of quercetin. Methods and results: A total of 32 aged ICR mice (15-month-old) and 16 young ICR mice (3-month-old) are randomly assigned into the following six groups: Young mice control group, young mice fed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 47 publications
2
43
2
Order By: Relevance
“…Quercetin [116], resveratrol [117] and ferulic acid [118] are other polyphenolic compounds isolated from vegetables and fruits with beneficial properties for AD treatment via inhibiting Aβ production/aggregation, destabilizing Aβ fibrils, alleviating oxidative stress and inflammation. Quercetin [119] and resveratrol [120] also rescued cognitive deficits by suppressing tau phosphorylation. In addition, resveratrol has been safe and well-tolerated for mild to moderate AD patients in two randomized, double-blind, placebo-controlled trials with uncertain efficacy on clinical outcomes [121,122], while quercetin and ferulic acid are not studied in clinical trials so far.…”
Section: The Main Redox Signaling-associated Mechanisms and Their Cromentioning
confidence: 92%
“…Quercetin [116], resveratrol [117] and ferulic acid [118] are other polyphenolic compounds isolated from vegetables and fruits with beneficial properties for AD treatment via inhibiting Aβ production/aggregation, destabilizing Aβ fibrils, alleviating oxidative stress and inflammation. Quercetin [119] and resveratrol [120] also rescued cognitive deficits by suppressing tau phosphorylation. In addition, resveratrol has been safe and well-tolerated for mild to moderate AD patients in two randomized, double-blind, placebo-controlled trials with uncertain efficacy on clinical outcomes [121,122], while quercetin and ferulic acid are not studied in clinical trials so far.…”
Section: The Main Redox Signaling-associated Mechanisms and Their Cromentioning
confidence: 92%
“…The results evaluating different biochemical pathways suggested that treatment by quercetin supplication has improved cognitive function in experimental animals. A similar study was carried out by Yang et al [103] by stating that extended application of quercetin may be beneficial for high consumers of dAGEs. The neurotoxicity by the exposure of pesticide fenitrothion has led Ibrahim et al [104], to carry out a study in rats for the role of quercetin against the development of such neurological impairment.…”
Section: Quercetin As a Neuroprotective Agentmentioning
confidence: 54%
“…To make high AGEs diet, the standard chow was baked at 180 ˚C for 60 min following a published method. [ 19,20 ] All diets were identical in macronutrients and calories, but HAGE diet contained more fluorescent AGEs (threefold), carboxymethyl lysine (CML; fivefold), and pentosidine (twofold) than LAGE diet (Table S1, Supporting Information). The mice were housed under a 12 h light/dark cycle with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%